Perilaku Toxic Masculinity di Kalangan Pelajar SMK - Nasution, Muhammad Rizqi Nurhysam; Nursanti, Siti; Lubis, Flori Mardiani (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Toxic masculinity behavior has become one of the examples of emerging reality in society. It talks about how a teenager male is bound to a long-formed social construction against the determination of attitudes and behaviors that men should be carrying out. Like a man should be strong, not crying, and so on. This study aims to identify toxic masculinity behavior that occurs among SMK students. The method used is qualitative research with a case study approach that is reviewed from Berger and Luckmann's theory of social reality construction and supported by Raewyn Connell's hegemonic masculinity theory. Subjects in this study were students of SMK Bina Karya 1 Karawang who consisted of five informants (three perpetrators and two victims) and selected on the basis of certain criteria. The data collection techniques used are observations, interviews and documentation.The results show that toxic masculinity in reality is based on three stages: externalization, objectification and internalization. At the externalization stage, the role of the family as well as the infancy of the informant becomes an important stage in the formation of their character as a man. Then at the objectivization stage, individuals begin to interact and see the reality that exists in their social environment through the meaning created for men. Lastly, the stage of internalization in which individuals embody existing subjectivity and become part of the members of society as a male.